Impact of Foreign Direct Investments on Serbian Industry - Boljanović, Srđan; Hadžić, Miroljub (Industrija, 2017)
The empirical researches to date on the impact of foreign direct investments (FDI) on the host country were either focused on the overall macroeconomic impact of FDI on exports of the host country or have analyzed the direct contribution of foreign affiliations or looked for spillover effects. By using a mixed model, the method of least squares (OLS) with fixed effects, in the paper has been proved that FDI had a positive effect on the growth of Serbian exports. FDI led to productivity growth in a large number of companies in the economy. At the same time the research conducted at the company level indicates the existence of horizontal and vertical spillover effects. FDI through vertical spillover effects had a positive effect on major suppliers while have led to significant displacement from the market of main competitors.